Standard Setting on Pesticide Residues to Ensure Food Safety - Lama, Jiwan Prava (Journal of Agriculture and Environment, 2009)
This article highlights some aspects of pesticides contamination in foods and the Government of Nepal's experience in setting MRLs of pesticide on Food. Use of pesticides in agriculture crop has a great concern to all. According to the provision conferred by Food Law, Government of Nepal fixes MRLs of pesticide on food products. Potential products liable for pesticide use gets priority in standard setting. The problem of pesticides begins at the farm level and continues at different stage of handling and storage. Therefore, effective coordination between stakeholders working with different stages of food handling must collaborate to solve this problem. In this connection, some major issues and recommendations in managing proper use of pesticides are highlighted. Key words: Pesticides, maximum residue limits (MRLs), Food safety and quality The Journal of Agriculture and Environment Vol:.9, Jun.2008 Page: 46-53